2002
DOI: 10.1073/pnas.142002099
|View full text |Cite
|
Sign up to set email alerts
|

Potent stimulation of transcription-coupled DNA supercoiling by sequence-specific DNA-binding proteins

Abstract: Transcription by RNA polymerase can stimulate localized DNA supercoiling in Escherichia coli. In vivo, there is extensive experimental support for a ''twin-domain'' model in which positive DNA supercoils are generated ahead of a translocating RNA polymerase complex and negative supercoils are formed behind it. Negative supercoils accumulate in the template DNA because the positive supercoils are preferentially removed by cellular topoisomerase action. Yet, in vitro, clear and convincing support for the twindom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 37 publications
6
80
0
Order By: Relevance
“…The transition is marked by a progressive collapse in the radius of gyration with increasing jsj above jsj z 0.08, during which branched hyper-supercoils become increasing prominent in the heterogeneous conformational population. This final supercoiling regime coincides with the maximum degree of supercoiling that is accessible by DNA gyrase (28) and occurs within the range of supercoiling densities generated upstream of translocating RNA polymerase in in vitro and in vivo transcription experiments (29,30,58). The R G distributions for the 10-kilobase dataset in Fig.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…The transition is marked by a progressive collapse in the radius of gyration with increasing jsj above jsj z 0.08, during which branched hyper-supercoils become increasing prominent in the heterogeneous conformational population. This final supercoiling regime coincides with the maximum degree of supercoiling that is accessible by DNA gyrase (28) and occurs within the range of supercoiling densities generated upstream of translocating RNA polymerase in in vitro and in vivo transcription experiments (29,30,58). The R G distributions for the 10-kilobase dataset in Fig.…”
Section: Resultssupporting
confidence: 58%
“…This rotation generates positively supercoiled DNA in front of the translocating transcription machinery, and leaves hypernegatively supercoiled DNA in its wake. Consistent with this model, both in vitro and in vivo studies indicate that RNA polymerase is a powerful torque generator, and linking deficits below s ¼ À0.10 have been measured as a result of transcription at strong promoters both in the presence of functional Topo I (DNA relaxing enzyme) as well as in Topo I-deficient mutants (28)(29)(30). Studies in E. coli and Salmonella have shown that RNA polymerase is capable of actively creating and remodeling dynamic supercoiled topological domains (6,33).…”
Section: Possible Implications For Transcriptional Control Of Chromosmentioning
confidence: 65%
See 3 more Smart Citations